Economic Dispatch Analysis Using Equal Incremental Cost Method with Linear Regression Approach - Hasibuan, Arnawan; Kurniawan, Robi; Isa, Muzamir; Mursalin, Mursalin (Institute for Research and Community Service, Universitas Malikussaleh, Indonesia, 2021)
The use of fuel is one thing that needs special attention, because most of the operating costs of a plant are fuel costs. One of the efforts to minimize the cost of generating fuel is called Economic dispatch. In this study, an Equal Incremental Cost method with a Linear Regression approach will be presented to obtain a minimum generation cost. The case taken is the Pangkalan Susu PLTU which operates two generating units. Based on the results of calculations using the Equal Incremental Cost method with the Linear Regression approach, the cost is -0.033% or an average of -13,111 /hour.